Pengaruh Penggunaan Media Loose Parts Terhadap Perkembangan Motorik Halus Anak Usia 5-6 Tahun Di PAUD Dahlia Rejasari - Herniawati, Ani; Rosidah, Lela (Sekolah Tinggi Ilmu Agama Islam Putra Galuh Ciamis, 2025)
Loose Parts is one of the media used to develop fine motor skill of early childhood aged 5-6 years. This study aims to determine the development of fine motor skill of early childhood aged 5-6 years before and after using Loose Parts media, and to determine the effect of using Loose Parts media on the development of fine motor skill of early childhood aged 5-6 years at PAUD Dahlia Rejasari. This study uses a quantitative method under a pre-experimental design. The results of the study assert that before being given treatment in the form of using the Loose Parts media, the development of early childhoods’ fine motor skill showed the results of “Beginning to Develop”. After being given treatment in the form of using the Loose Parts media, the development of early childhoods’ fine motor skill showed the results of “Developed Very Well”. Meanwhile, based on the results of the t-test, it is stated that t-count> t-table, which shows 9.454> 2.201 at a significance level of 0.05, at which H0 is rejected and H1 is accepted. The data confirms that there is an effect of using the Loose Parts media on the development of fine motor skill of early childhood aged 5-6 years at PAUD Dahlia Rejasari.